2013
DOI: 10.1186/1471-2334-13-400
|View full text |Cite
|
Sign up to set email alerts
|

Differential arthritogenicity of Staphylococcus aureusstrains isolated from biological samples

Abstract: BackgroundStaphylococcus aureus is the most common agent of septic arthritis that is a severe, rapidly progressive and destructive joint disease. Superantigens produced by S. aureus are considered the major arthritogenic factors. In this study, we compared the arthritogenic potential of five superantigen-producing staphylococcal strains.MethodsMale C57BL/6 mice were intravenously infected with ATCC 19095 SEC+, N315 ST5 TSST-1+, S-70 TSST-1+, ATCC 51650 TSST-1+ and ATCC 13565 SEA+ strains. Clinical parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Colavite-Machado et al described the weight loss after 3, 7, and 14 days of infection in S. aureus-infected mice [31]. Similarly, we observed a significant weight loss after 24 hours post-infection in BSI mice (p < 0.001) ( Table 1).…”
Section: Weight Losssupporting
confidence: 66%
“…Colavite-Machado et al described the weight loss after 3, 7, and 14 days of infection in S. aureus-infected mice [31]. Similarly, we observed a significant weight loss after 24 hours post-infection in BSI mice (p < 0.001) ( Table 1).…”
Section: Weight Losssupporting
confidence: 66%
“…In murine models, there is a rapid recruitment of neutrophils, mediated by formylated peptides (465), after S. aureus gains entry to the joint space. Activated macrophages and T cells are recruited as well, and a host of cytokines are induced, including tumor necrosis factor alpha (TNF-␣), gamma interferon (IFN-␥), interleukin-1 (IL-1), IL-2, IL-6, and IL-17 (466). Neutrophils, however, play a dual role.…”
Section: Septic Arthritismentioning
confidence: 99%
“…The results of this study have confirmed the role of S. aureus in the development of RA disease. The results of another study revealed that intravenous administration of S. aureus strains such as ATCC 19095 SEC+, N315ST5 TSST-1+, and ATCC SEA+ could cause progressive arthritis in mice ( 13 ). On the other hand, the results of the research showed the staphylococcal superantigens arthrogenicity activity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we assume that the existence of superantigens in the body fluid of patients may have endogenous origin, because in previous studies, the existence of S. aureus enterotoxins in patients’ synovial fluid with RA was demonstrated ( 11 , 12 ). Moreover, superantigens produced by S. aureus are considered as major arthritogenic factors ( 13 ).…”
Section: Introductionmentioning
confidence: 99%